2008
DOI: 10.2298/vetgl0802077t
|View full text |Cite
|
Sign up to set email alerts
|

Presence of thermophilic Campylobacter species in Broilers and pigs at certain abattoirs in Republic of Serbia

Abstract: Examinations were carried out during the period from January 2006 until March 2007 on a total of 449 samples of the cecum of broilers and the cecum and the colon of pigs. These samples included 251 samples originating from broilers and 198 samples of pig cecums and colons. All the listed samples were obtained by scraping the surface of these parts of the digestive system of broilers and pigs. At the site of sampling, the diluted material was sown on a medium (Karmali agar), in order to get individual colonies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…than poultry. A similar result has been obtained in a study performed in Serbia (Tambur et al, 2008).…”
Section: Introductionsupporting
confidence: 90%
“…than poultry. A similar result has been obtained in a study performed in Serbia (Tambur et al, 2008).…”
Section: Introductionsupporting
confidence: 90%
“…Swines are less than poultry colonized by the same bacteria. Tambur et al 9 demonstrated that 80.88% of poultry and 77.27% of swines are contaminated by thermophilic Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%